METHODOLOGY FOR RESEARCHING THE INCLUSIVENESS OF HIGHER EDUCATION - Zapukhliak, Ivanna Bogdanivna; Маланюк, Назарій Ігорович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article deals with the concepts of inclusion, inclusive environment, and inclusive education. It is substantiated that ensuring the inclusiveness of higher education is relevant both from the point of view of sustainable development of the higher education system and from the point of view of meeting the requirements of the present due to the war. The process of forming the legal and regulatory framework for an inclusive environment in higher education, from the ratification of the relevant UN Convention to the Strategy for the Development of Inclusive Education in Ukraine, is studied, which allowed to identify the problems that exist today in the field of education. It has been established that today the country's legislation does not cover all categories of persons with special needs. There are also a number of problems in creating access conditions for people with special needs, applying appropriate types, forms and methods of education, taking into account individual needs and capabilities, creating individual development and training programs, ensuring the participation of psychological services in the education and life of people with special needs, etc. We believe that the primary task is to research and formulate a regulatory, legal, methodological, educational, informational, and logistical environment at the level of higher education institutions to meet the requirements of inclusiveness. The methodological foundations of the study of the inclusiveness of higher education are proposed, starting with the formulation of problems, goals, principles and objectives of the study; clarification of the concepts of “inclusion of higher education”, “inclusive environment”; formation of categories of persons with special needs, groups of stakeholders; formation of indicators for assessing the level of inclusiveness of higher education, research methods. We believe that it is the application of a scientific approach to the formation of inclusive higher education that can ensure the creation of new theoretical knowledge and practical solutions to increase the level of barrier-free access to higher education for people with special needs and maximize the results of their education.